Factors Influencing the Adoption of Digital Banking: Generation Z in Surabaya - Kurniawan, Abraham Ivan; Morgan Gemiartha, Celine; Edbert Sudarsono, Jethson; Wijaya, Joshua; Adeline Yusuf, Keona; Linawati, Nanik (DINASTI RESEARCH, 2025)
The study titled